The composition of the lower oceanic crust in the Wadi Khafifah section of the southern Samail (Oman) ophiolite - VanTongeren, Jill; Kelemen, Peter; Garrido, Carlos; Godard, Marguerite; Hanghoj, Karen; Braun, Michael; Pearce, Julian (Dryad, 2021)
The composition of the intrusive gabbroic lower oceanic crust remains
poorly characterized in comparison to the extrusive portion of the oceanic
crust, especially for intermediate-fast spreading mid-ocean ridges. This
is a consequence of limited exposures of extant lower oceanic crust and of
ophiolites similar to mid-ocean ridge crust. One of the best
analogues for mid-ocean ridge crust is the southern Samail ophiolite that
formed during a period of rapid seafloor spreading above a nascent
subduction zone. Here, we focus on the geochemical stratigraphy
(whole rock and mineral major and trace element compositions) of the 5200
m-thick, lower crustal, Wadi Khafifah section of the Wadin Tayin massif in
the southern Oman ophiolite. Gabbros from the lowermost 3700 m of
this section (the 'lower gabbros') show no systematic changes in
composition with height above the Mantle Transition Zone. In contrast,
gabbros from the uppermost 1500 m (the 'upper gabbros') display
marked increases in incompatible trace element concentration with
increasing height. Liquids in equilibrium with the lower gabbros
have major and trace element compositions that overlap with those measured
in the upper gabbros and sheeted dikes. Upper gabbros preserve mineral
cores with primitive major element compositions that overlap with the
range of lower gabbros, however, upper gabbro whole rock compositions are
significantly more enriched in incompatible trace elements relative to the
lower gabbros. Our data reveal that the upper gabbros are a
composite of accumulated minerals derived from primitive melts and a large
fraction of evolved melts derived from the fractionation of the lower
gabbros. We propose a new “Full Sheeted Sills” model for the
lower oceanic crust in which primitive magmas from the mantle are emplaced
throughout the lower crust and crystallized in situ. After diking
events, evolved magmas leave the lower gabbros and replenish the upper
gabbros, thereby contributing to the higher incompatible trace element
budget in the upper gabbros relative to the lower gabbros. Our
reconstructed bulk compositions of the lower plutonic crust and the bulk
oceanic crust from the Wadi Khafifah section yield a plausible primary
mantle-derived magma composition in equilibrium with depleted MORB mantle.
All gabbro samples measured here are exceptionally fresh and largely free
of low temperature alteration or metasomatism (Fig. 4b). Sheeted dike
samples were collected from a similar location to those studied by
Pallister and Hopson (1981)(Table 1b). All 33 sheeted dike
samples reported here are slightly to moderately altered at greenschist
facies, but preserve chilled margin contacts and provide reliable
compositions for comparision here for all but the more fluid-mobile
elements. 3. 1 Compositional Analyses We report data from 33 lower crustal
samples spaced on average every 50-100 m through the lower crust
stratigraphy, except for a stratigraphic sampling gap occurring between
2369 m and 2999 m. Whole rock major element compositions for
gabbro and sheeted dikes lithologies were determined by XRF at the
Washington State Geoanalytical Laboratory (Table 2). Trace
element concentrations were determined by Inductively Coupled Plasma Mass
Spectrometry (ICPMS) at the Université de Montpellier (the gabbros) and
Cardiff University (the dikes). Compositions of the major rock forming
minerals were determined by electron microprobe analysis (EPMA) at the
Massachusetts Institute of Technology JEOL EPMA facility and the American
Museum of Natural History Cameca EPMA facility. Major and minor elements
in pyroxenes (Table 3) and olivines (Table 4) were analyzed with 20nA,
15KeV beam, and 30 sec on peak and 15 sec on background. Major
and minor elements in plagioclase (Table 5) were analyzed with a 10nA, 15
keV beam with 30 sec on peak and 15 sec on background. Modal
abundances of minerals were determined by the least squares method using
the major element compositions of the whole rock and its consituent
minerals. This method does not distinguish between cumulus and
intercumulus mineral abundances. Trace element concentrations of
plagioclase (Table 6) and clinopyroxene (Table 7) were measured by Laser
Ablation ICPMS (LA-ICPMS) at Rutgers University. For plagioclase, we used
a spot size of 65 microns and a fluence of 5.32 J/cm2. For
pyroxene, we used a spot size of 40 microns and fluence of 2.95 J/cm2.
Standards NIST 610, 612, and 614 were used to construct calibration
curves, and basalt glasses BCR and BIR were regularly analyzed as unknowns
to ensure accuracy. All data presented represent averages of mineral
cores. No mineral rims were measured in this study.
Keywords: FOS: Earth and related environmental sciences